Effects of Embryo Microbial Contamination on ART and Neonatal Outcomes - He Y; Mao Y; Chen Y; Tang L; Hou H; Sun C; Shang Y; Tan NN; Li L (Infection and Drug Resistance, 2024)
Yuxia He,1,2,* Yuling Mao,1,2,* Yaoming Chen,3,* Ling Tang,1 Haiyu Hou,1 Chenyun Sun,1 Yaqi Shang,1 Na-Na Tan,4 Lei Li1,2 1Department of Obstetrics and Gynecology, Center for Reproductive Medicine; Guangdong Provincial Key Laboratory of Major Obstetric Diseases; Guangdong Provincial Clinical Research Center for Obstetrics and Gynecology; Guangdong-Hong Kong-Macao Greater Bay Area Higher Education Joint Laboratory of Maternal-Fetal Medicine; The Third Affiliated Hospital, Guangzhou Medical University, Guangzhou, People’s Republic of China; 2Key Laboratory for Reproductive Medicine of Guangdong Province, The Third Affiliated Hospital of Guangzhou Medical University, Guangzhou, People’s Republic of China; 3Department of Laboratory Medicine, The First Affiliated Hospital of Sun Yat-Sen University, Guangzhou, People’s Republic of China; 4Department of Health Management; Guangdong Provincial Key Laboratory of Major Obstetric Diseases; Guangdong Provincial Clinical Research Center for Obstetrics and Gynecology; The Third Affiliated Hospital, Guangzhou Medical University, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lei Li; Na-Na Tan, Email lileigo@foxmail.com; tannana0212@126.comPurpose: This study investigated the incidence and microbial etiology of embryo contamination in assisted reproductive technology (ART), and its influence on embryo development, pregnancy and neonatal outcomes.Methods: A retrospective analysis was conducted on embryo contamination at the Reproductive Centre of the Third Affiliated Hospital of Guangzhou Medical University, between 2018 and 2021.Results: In the period from 2018 to 2021, the average incidence of embryo contamination was 0.12%. Bacterial growth was observed in 39 cases, with a preponderance of Escherichia coli (20, 51.28%), Streptococcus agalactiae (7, 17.95%). The fertilization rate of contaminated embryos was 18.18% (Klebsiella pneumoniae) to 94.79% (S. agalactiae), the cleavage rate was 9.09% (Enterobacter cloacae) to 98.90% (S. agalactiae), and the available embryo rate of Day 3 was 0 (Klebsiella pneumoniae, Enterobacter cloacae) to 63.33% (S. agalactiae). Blastocyst formation rate was 3.23% (Proteus mirabilis) to 64.29% (Streptococcus mitis). E. coli contamination occurred mostly on Day 1, and S. agalactiae on Days 3 and 5. After rinsing and rescuing treatment, six healthy male babies were born.Conclusion: E. coli and S. agalactiae were the most common bacterial embryo contaminants. Most microbial contamination can significantly decrease the fertilization rate. Embryo transfer after rinsing and continuing culture had no negative effect on neonatal outcomes, but there was an increased risk of early abortion due to E. coli contamination.Keywords: in vitro fertilization, microbial contamination, remedial treatment, pregnancy outcome, neonatal outcomes